Learning (to teach) English for Academic Purposes in pre-service teacher education - Sarmento, Simone; Vial, Ana Paula Seixas (Letras, 2022)
The aim of this study is to examine how inexperienced English teaching degree students deal with the challenge of having simultaneously to learn about and to deliver courses of academic English. Data was generated through participant observation in teacher development sessions of a language center located in a public university in Brazil. The results suggest that student teachers learned both English for Academic Purposes and how to teach it by studying and producing academic genres, by sharing their knowledge with their peers, and by reflecting collectively on their teaching practices.